IoT with Firebase: Smart Ring Android App Using MAX30100 for Fatigue Detection - Liptia Venica; Elysa Nensy Irawan; Dewi Indriati Hadi Putri (Universitas Sebelas Maret (UNS), 2024)
IoT in healthcare enables real-time health monitoring & data evaluation of patient conditions. One of the benefits of IoT wearable devices is protecting a person from getting exhausted. Body fatigue is an indicator of the emergence of several problems such as sudden attacks of dangerous diseases, accidents, and so on. The large number of deaths from various diseases and accidents that are triggered by body fatigue makes monitoring the level of body fatigue important to minimize this. Through this research, we proposed the Smart Ring; a tool for monitoring and evaluating the level of body fatigue using a wearable sensor and based on the Internet of Things (IoT). In this article, we focus on developing the software component (Android application) and database management system of the Smart Ring IoT system. Age, heart rate, SpO2, and body temperature are used as indicators to determine user’s body condition categories. These data are collected through sensors on hardware part of Smart Ring System. The proposed database management system is able to store collected data inside NoSQL database in the form of documents. Smart Ring Android-based application is capable to monitor three user’s body condition and evaluate them to predict the user’s condition with classification accuracy of 100% within the defined categorization rules. It offers real-time user monitoring for exhaustion signs and triggering timely alerts with sub-2-second data processing under ideal conditions. The proposed Smart Ring system is expected to become an easy to develop, economical and portable medical device which help improve the welfare of society 5.0 in the health sector.